Post-transcriptional Regulation of PCSK9 by miR-191, miR-222, and miR-224 - Naeli, Parisa; Mirzadeh Azad, Fatemeh; Malakootian, Mahshid; Seidah, Nabil G.; Mowla, Seyed J. (Frontiers in Genetics, 2017)
Since the discovery of the proprotein convertase subtilisin kexin 9 (PCSK9), a gene product involved in LDL metabolism regulation and cardiovascular diseases (CVD), many therapeutic strategies have been introduced for direct targeting of PCSK9. The main goal of these strategies has been to reduce PCSK9 protein levels either by injectable inhibitory antibodies or blockade of its production. In this study, we have tried to discover microRNAs (miRNAs) which can target, and hence regulate, PCSK9 expression. Using bioinformatics tools, we selected three microRNAs with predicted binding sites in the 3ʹ-UTR of PCSK9. The expression level of these miRNAs was examined in three different cell lines using real-time RT-PCR. We observed a reciprocal expression pattern between the RNA levels of miR-191, miR-222 and miR-224 and that of PCSK9. Accordingly, the expression levels of these miRNAs' were highest in Huh7 cells, which expressed the lowest level of PCSK9, as compared to HepG2 and A549 cell lines. PCSK9 mRNA levels were significantly reduced in HepG2 cells overexpressing the aforementioned miRNAs. Furthermore, these miRNA target sites were cloned in a psiCHECK-2 vector, and a direct interaction of the miRNAs and the PCSK9 3ʹ-UTR putative target sites were assessed using a luciferase assay. Our findings demonstrated that miR-191, miR-222 and miR-224 can directly interact with PCSK9 3ʹ-UTR and reduce its expression. In conclusion, our data provided evidence for three specific miRNAs that down-regulate PCSK9 expression.